The Effect of Keyboard Key Spacing on Typing Speed, Error, Usability, and Biomechanics, Part 2: Vertical Spacing. (June 2014) - Pereira, Anna; Hsieh, Chih-Ming; Laroche, Charles; Rempel, David
Objective: The objective was to evaluate the effects of vertical key spacing on a conventional computer keyboard on typing speed, percentage error, usability, forearm muscle activity, and wrist posture for both females with small fingers and males with large fingers. Background: Part 1 evaluated primarily horizontal key spacing and found that for male typists with large fingers, productivity and usability were similar for spacings of 17, 18, and 19 mm but were reduced for spacings of 16 mm. Few other key spacing studies are available, and the international standards that specify the spacing between keys on a keyboard have been mainly guided by design convention. Method: Experienced female typists ( n = 26) with small fingers (middle finger length ≤ 7.71 cm or finger breadth of ≤ 1.93 cm) and male typists ( n = 26) with large fingers (middle finger length ≥ 8.37 cm or finger breadth of ≥ 2.24 cm) typed on five keyboards that differed primarily in vertical key spacing (17 × 18, 17 × 17, 17 × 16, 17 × 15.5, and 18 × 16 mm) while typing speed, error, fatigue, preference, forearm muscle activity, and wrist posture were recorded. Results: Productivity and usability ratings were significantly worse for the keyboard with 15.5 mm vertical spacing compared to the other keyboards for both groups. There were few significant differences on usability ratings between the other keyboards. Reducing vertical key spacing, from 18 to 17 to 16 mm, had no significant effect on productivity or usability. Conclusions: The findings support the design of keyboards with vertical key spacings of 16, 17, or 18 mm. Applications: These findings may influence keyboard design and standards.